2018
DOI: 10.1002/ps.5200
|View full text |Cite
|
Sign up to set email alerts
|

Novel film‐forming formulations of the biocontrol agent Candida sake CPA‐1: biocontrol efficacy and performance at field conditions in organic wine grapes

Abstract: The results of this work suggest that solid formulations would be a competitive alternative to conventional fungicides because they were easy to package and transport, and cell viability could be maintained for a long period of time. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…Despite the low resilience of C. sake CPA-1 at temperatures higher than 30 ∘ C, the efficacy of fluidized-bed spray-dried formulations was demonstrated under field conditions on grapes, where maximum temperatures were higher than 35 ∘ C. 19 In contrast, C. sake CPA-1 was isolated from apples after several months in a storage atmosphere 1 and the present study showed that the PS and MAL formulations maintained their viability after 30 days at 0 ∘ C regardless of the RH. It may therefore be possible to consider both preharvest and postharvest application as registered uses for the products.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Despite the low resilience of C. sake CPA-1 at temperatures higher than 30 ∘ C, the efficacy of fluidized-bed spray-dried formulations was demonstrated under field conditions on grapes, where maximum temperatures were higher than 35 ∘ C. 19 In contrast, C. sake CPA-1 was isolated from apples after several months in a storage atmosphere 1 and the present study showed that the PS and MAL formulations maintained their viability after 30 days at 0 ∘ C regardless of the RH. It may therefore be possible to consider both preharvest and postharvest application as registered uses for the products.…”
Section: Discussionmentioning
confidence: 97%
“…The efficacy of both novel film‐forming formulations of CPA‐1 was demonstrated against B. cinerea on grapes in a laboratory‐based assay . The incidence and severity of gray mold and the severity of sour rot were significantly reduced under field conditions during two growing seasons . Botrytis cinerea produces significant losses in more than 200 crops worldwide with over 1400 plant species as possible hosts .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations